Effect of accumulative roll bonding process on textural evolution and its comparison with normal rolled AA7005 aluminum alloy - Xie H.; Wang M.P.; Chen W.; Du Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present work, texture evolution of AA7005 aluminum alloy during the accumulative roll bonding and conventionally rolled was investigated by X-ray diffraction. It was found that the dominant texture components of both samples were Brass, Copper, Rotated Cube and Goss components, but the ARB texture evolution was quicker and displayed complex features. When the number of ARB cycle increased, the intensity of texture components decreased at the second and third pass, then enhanced at the fourth pass, and finally decreased. During the ARB process there was a texture transition at the second and third pass from Brass and S to Rotated Cube components due to the shear texture which formed on the surface region and moved to the center during the next pass. The enhancement of texture intensity at the fourth pass might be attributed to the formation of nano shear bands. The texture intensity decreasing at final cycle was correlated to redundant shear strain and continuous recrystallization during the high ARB passes.